PERBANDINGAN PROTEKSI TIANG PANCANG MENGGUNAKAN FIBER REINFORCED POLYMER DAN HIGH DENSITY POLYETHYLENE - Philbert Manuel Roosevelt Hutapea; Arianti Sutandi (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Piles are a very important foundation for port docks. Like steel and reinforced concrete foundations, they have a limited service life when used in harsh marine environments. Chemical and biological factors are problems that often arise in dock piles. Chemical factors such as corrosion and biological factors such as the growth of marine life. For this reason, pile protection is needed such as High Density Polyethylene jacket pile dan Fiber Reinforced Polymer composite as pile protectors, so that the piles can function according to their design life. This research was conducted to determine the comparison between Fiber Reinforced Polymer and High Density Polyethylene jacket pile composites in terms of execution time, implementation costs, and long term conditions. In terms of execution time, the installation of Fiber Reinforced Polymer composites is faster than High Density Polyethylene jacket piles, while in terms of implementation costs, Fiber Reinforced Polymer composites cost 6.4% more than High Density Polyethylene. Lastly, in terms of conditions in the field, Fiber Reinforced Polymer composite has not found any damage in a period of 5 years, while High Density Polyethylene jacket pile has found non-technical damage in a period of 8 years and 10 years. Abstrak Tiang pancang merupakan suatu fondasi yang sangat penting bagi dermaga pelabuhan. Seperti fondasi baja dan beton bertulang, memiliki umur pemakaian yang terbatas bila digunakan di lingkungan laut yang keras. Faktor kimia dan biologis merupakan permasalahan yang sering timbul pada tiang pancang dermaga. Faktor kimia seperti korosi dan faktor biologis seperti tumbuhnya biota laut. Untuk itu diperlukan proteksi tiang pancang seperti High Density Polyethylene jacket pile dan Fiber Reinforced Polymer composite sebagai pelindung tiang pancang, sehingga tiang pancang dapat berfungsi sesuai dengan umur desainnnya. Penelitian ini dilakukan untuk mengetahui perbandingan antara Fiber Reinforced Polymer composite dan High Density Polyethylene jacket pile dari segi waktu pelaksanaan, biaya pelaksanaan, serta kondisi pada jangka waktu yang lama. Dari segi waktu pelaksanaan, pemasangan Fiber Reinforced Polymer composite lebih cepat dibandingkan dengan High Density Polyethylene jacket pile sedangkan dari segi biaya pelaksanaan, Fiber Reinforced Polymer composite memiliki biaya yang lebih besar 6,4% dibandingkan dengan High Density Polyethylene. Dan dari segi kondisi di lapangan, Fiber Reinforced Polymer composite belum ditemukan adanya kerusakan pada jangka waktu 5 tahun, sedangkan High Density Polyethylene jacket pile sudah ditemukan kerusakan secara non-teknis pada jangka waktu 8 tahun dan 10 tahun.